REAKSI PASAR TERHADAP KEBIJAKAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) LEVEL 4 PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Devinda Larasati; Nur Diana; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this research was to determine the market reaction to Trading Volume Activity and Stock Returns before and after the implementation of Level 4 Community Activity Restrictions (PPKM) on LQ-45 companies listed on the Indonesia Stock Exchange. Quantitative research design was adopted in this study, this study collected secondary data. This study used a purposive sampling method and the number of participants was 43 LQ-45 companies listed on the IDX for 20 days before and 20 days after the implementation of the restriction on community activities (PPKM) Level 4. Hypothesis testing was carried out using a paired sample t test. The results of this study based on hypothesis testing on a paired sample t test showed that the average stock return before and after the announcement of PPKM Level 4 showed an asymptotic significance value (2-tailed) of 0.986. The value is > 0.05 which means there is no significant difference between before and after the implementation of PPKM Level 4 on Stock Return. And the average Trading Volume Activity (TVA) before and after the announcement of PPKM Level 4 showed an asymptotic significance value (2-tailed) of 0.013. The value is < 0.05 which means there is a significant difference between before and after the implementation of PPKM Level 4 on Trading Volume Activity (TVA).Keywords: Trading Volume Activity, Return Saham, Level 4 Community Activity Restrictions